SELF-REGULATED LEARNING IN WRITING A Case Study of Students from Different Achievement Tracks - Habil Maseh Maulid, - (2019)
Self-Regulated Learning (SRL) has been a major interest for many educational researchers as it assists students to be more competent and autonomous in language learning. This study aims to investigate the SRL strategies of students from different achievement tracks through writing activity and their response to the strategies during the activity. It was conducted to provide teachers with the description of students' SRL strategies that promote their success in learning, specifically in English writing activity. Using a qualitative case study design, this study attempted to employ two instruments with the focus of three Indonesian undergraduate students in an English Course. The instruments included Self-Regulated Learning Interview Schedule (SRLIS), and structured-diary form. The result of this study presents at least eight SRL strategies used during the process of writing composition. Additionally, students with lower achievement tracks employed more strategies than students with higher achievement tracks did. Ultimately, this study suggests that instructional support of SRL from teachers might be critical as it promotes effective learning environment, specifically in writing.